Analysis Comparative of Stock Prices and Stock Trading Volume Before and After the Reverse Stock Split in Companies Listed on The Indonesia Stock Exchange For The Period 2015-2022 - Alwi Ihsan Nababan; Rizma Nazriah Hasibuan (CV. ADMITECH SOLUTIONS, 2025)
The purpose of this study is to examine and analyze the comparison of stock prices and stock trading volume before and after a reverse stock split in companies listed on the Indonesia Stock Exchange during the period 2015-2022. This research adopts an event study approach, which investigates market reactions to specific events, in this case, reverse stock splits. The population in this study consists of all companies listed on the Indonesia Stock Exchange that conducted a reverse stock split between 2015 and 2022. Using a purposive sampling method, 13 companies were selected as the research samples based on specific criteria. The data analysis techniques used in this study include the Paired Sample T-Test and the Wilcoxon Signed Rank Test. The Paired Sample T-Test is applied to determine whether there is a statistically significant difference in stock prices before and after the reverse stock split. Meanwhile, the Wilcoxon Signed Rank Test is used to analyze the differences in stock trading volume before and after the event. The results of the study indicate that, based on the Wilcoxon Signed Rank Test, there is no statistically significant difference in stock prices before and after the reverse stock split. However, the analysis reveals a significant difference in stock trading volume before and after the reverse stock split, suggesting that the event had a notable impact on trading activity but not on stock price levels.